The Study of Prevalence of Helicobacter Pylori in Patients with Acne Rosacea - Bhattarai, S; Agrawal, S; Rijal, A; Majhi, S; Pradhan, B; Dhakal, SS (Kathmandu University Medical Journal, 2014)
Background Acne rosacea is an inflammatory disease affecting the central part of the face characterized by erythema, papules, papulo pustules and telangiectasias of unknown etiology. More recently numerous studies have described an association with Helicobacter pylori (Hp) and the extra gastric symptoms of cutaneous origin. Objectives To establish the prevalence of Helicobacter pylori (Hp) infection in the stomach in patients with rosacea based on standard Hp serological test. Methods All patients with the clinical staging of 2, 3 and 4 rosacea attending the Dermatology Out Patient Department from May 2009 – April 2010 were included in the study. Quantitative serological test using the SERION ELISA classic Helicobacter pylori IgG was done. Result A total of 26 patients were enrolled in the study with the age ranging from 26- 82 years. There were 14 males and 12 females and the male: female ratio was 1.6:1. Three (11.53%) patients presented with Grade IV rosacea, a severe clinical presentation and symptoms suggestive of acid peptic diseases were found in 14/26 (53.8%) patients. A positive serology to H. pylori was found in 17/26 (65.4%) of patients. A statistically significant correlation was found when association of H.pylori positivity in patients of rosacea compared with the seropositivity in controls. However correlation in the seropositivity was not found amongst the patients having gastritis and rosacea. Conclusion There still proves to find a correlation of Hp infection with patients with rosacea but it can still be hypothesised as a cutaneous manifestation of an internal peptic ulcer disease . DOI: http://dx.doi.org/10.3126/kumj.v10i4.10995 Kathmandu Univ Med J 2012;10(4):49-52